2007
DOI: 10.1073/pnas.0709971104
|View full text |Cite
|
Sign up to set email alerts
|

A biochemical approach to identifying microRNA targets

Abstract: Identifying the downstream targets of microRNAs (miRNAs) is essential to understanding cellular regulatory networks. We devised a direct biochemical method for miRNA target discovery that combined RNA-induced silencing complex (RISC) purification with microarray analysis of bound mRNAs. Because targets of miR-124a have been analyzed, we chose it as our model. We honed our approach both by examining the determinants of stable binding between RISC and synthetic target RNAs in vitro and by determining the depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
305
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(315 citation statements)
references
References 23 publications
(29 reference statements)
9
305
0
1
Order By: Relevance
“…We used a similar microarray-based analysis to identify mouse mRNAs downregulated by mature miR-124 or the miR-124-UU21 variant in undifferentiated P19 cells. The mRNAs downregulated by miR-124 were consistent with other reports, and included known targets of miR-124 [41] [47] [43] [81]. Comparison of mRNAs downregulated by miR-124 and miR-124-UU21 showed surprisingly limited overlap between mRNAs regulated by each miRNA.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We used a similar microarray-based analysis to identify mouse mRNAs downregulated by mature miR-124 or the miR-124-UU21 variant in undifferentiated P19 cells. The mRNAs downregulated by miR-124 were consistent with other reports, and included known targets of miR-124 [41] [47] [43] [81]. Comparison of mRNAs downregulated by miR-124 and miR-124-UU21 showed surprisingly limited overlap between mRNAs regulated by each miRNA.…”
Section: Discussionsupporting
confidence: 89%
“…Cao et al [44] observed defects in the basal lamina in response to ectopic miR-124 expression in chicken neural tube, and they linked these defects to reduced expression of integrin β1 and laminin proteins. In addition, since miRNAs can inhibit translation without reducing mRNA levels, it is likely that there are additional miR-124 target genes yet to be identified [81].…”
Section: Discussionmentioning
confidence: 99%
“…4A and Table S8 lists all transcript data). Recent reports using Ago-2 to pull down miRNA targets in mammalian cells over-expressing a miRNA also showed limited overlap with targets downregulated at the mRNA level (20,23). To explore the basis for these differences we examined the two groups for distinct structural and molecular features, using all S2 mRNAs as a common control set.…”
Section: Comparison Of Targets Identified By Ago1 Ip and Ago1 Depletionmentioning
confidence: 99%
“…One such alternative involves identification of microRNA targets by virtue of their physical association with miRNAcontaining ribonucleoprotein complexes (19)(20)(21)(22)(23)(24). In ref.…”
mentioning
confidence: 99%
“…In such a experiment, we don't know which mRNAs are targets of which miRNA. To overcome this problem, the overexpression or inhibition of miRNA before the immunoprecipitation and comparison with control by microarray analysis will be useful (Karginov et al, 2007;Chi et al, 2009). cancer.…”
Section: Biogenesis Of Mirnas and Gene Regulation By Mirnasmentioning
confidence: 99%